MEDIA LITERACY IN THE MODERN EDUCATION SYSTEM - Akbar Safarov (Zeta Repository, 2023)
In an article about the fact that today there is a growing need for media literacy in order to separate the necessary information from the unnecessary. So what is media literacy? Why is its importance growing today? The rapid increase in the flow of information in recent years, as well as the increase in both positive and negative information, requires media literacy.